MORPHOMETRIC ANALYSIS OF THE HAND - RAMESWARAPU SUMAN BABU; DAVID ANAND KUMAR .P (International Journal of Pharma and Bio Sciences, 2013)
This study is an analysis of the patterns of variation of the human hand, particularly the metric characters of hand, palm, fingers, nails and dorsal distribution of hair over the digits. Anthropometric measurements were performed on 124 men and women, aged 21 to 41 years in and around medchal town. The data were analyzed by inferential statistics. Size variation in fingers is indicated in the present study. There is component of variability between all fingers as a whole and distal phalanges, the variation is much between the thumb and other fingers. Sexual dimorphism is proven fact as menhave greater dimensions than women in length of the thumb than other fingers.